Mental health care: a challenge to guarantee safe and healthy work environments - Quiñones Infante, Sergio (2024)
This paper is aimed to analyze the strong link that exists between the implementation of appropriate measures to care for the mental health of workers in the workplace and the effective compliance by employers with guaranteeing a safe and healthy environment in all work centers. With this purpose, we begin by developing the applicable theoretical framework within which the concept of “mental health at work” is framed; subsequently, we analyze data about the current state of this public problem, both at a global and national level, placing particular emphasis on those investigations that show the negative impact that inadequate mental health care generates on the work productivity of workers. Finally, we will evaluate the current and future challenges that mental health care at work presents from the perspective of public policies and from the perspective of business organizations.